Awareness of Autism among Primary Educators in Rural Andhra Pradesh - Supriya Rayana (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: This study aims to assess the knowledge of autism among elementary school teachers in and around the coastal belt of Andhra Pradesh. Materials and Methods: This descriptive cross-sectional observational study was conducted in 137 elementary schools in the coastal districts of Andhra Pradesh, India. Data were collected using a validated questionnaire encompassing foundational knowledge, social and communication behavior, emotional characteristics, and physical health-related issues. Results and Discussion: A total of 319 subjects participated in the study. The highest level of awareness has been identified in foundational knowledge, at 47%, whereas physical and health-related issues scored the lowest at 37%. While 54.84% of participants were aware that autism is a developmental disorder, only 33.33% recognized gastrointestinal issues in children who have an autism disorder. There is no considerable difference in awareness noticed between educators at public and private educational institutions, except for Q.18 (P = 0.000028). Conclusion: Awareness levels between age categories and educational settings were assessed. These findings suggest the significance of regular academic programs to improve. Awareness of autism spectrum disorder (ASD) among caregivers. Enhancing awareness of early signs, behavioral characteristics, and associated conditions can significantly support early diagnosis and better treatment for children diagnosed with ASD.